Long-term improvement of quality of life in adult ADHD – results of the randomized multimodal COMPAS trial. Issue 3 (3rd July 2021) - Lücke, Caroline; Jenkner, Carolin; Graf, Erika; Matthies, Swantje; Borel, Patricia; Sobanski, Esther; Alm, Barbara; Rösler, Michael; Retz, Wolfgang; Jacob, Christian; Colla, Michael; Huss, Michael; et al.
Abstract: Attention Deficit Hyperactivity Disorder (ADHD) negatively impacts Quality of Life (QoL) in adults. Earlier studies on pharmacological treatment have shown short-term beneficial effects on QoL. No data are available on long-term effects on multimodal psychosocial and/or pharmacological interventions. The Comparison of Methylphenidate and Psychotherapy in Adult ADHD Study (COMPAS), a prospective, multicenter randomized clinical trial, compared cognitive behavioral group psychotherapy (GPT) with individual clinical management (CM) and methylphenidate (MPH) with placebo (Plac) (2 × 2 factorial design over a period of 52 weeks). Change of QoL was measured after three months of intensive treatment, after 26 weeks, and after one year of maintenance treatment, using the Quality of life enjoyment and satisfaction questionnaire (Q-LES-Q, eight subscales). A follow-up was performed 1.5 years after treatment completion. Q-LES-Q scores were analyzed descriptively (means and confidence intervals). A linear regression model was used to test for significant differences between the four treatment arms. The full analysis set comprised 419 patients. Q-LES-Q scores increased between baseline and the end of treatment across all Q-LES-Q subscales (with exception of stable scores in the physical health/activities subscale in the CM + Plac group) and remained stable improved at follow-up. Regression analyses did not show any significant differences between the four treatment conditions. COMPAS is the first study to demonstrate stable and long-term improvements of QoL after multimodal treatment regardless of medication with MPH or Placebo, and regardless of structured GPT or individual CM. Trial registration: ISRCTN54096201